Lie and Jordan Structure in Prime Γ- rings with Γ-centralizing Derivations - Majeed, Abdulrahman; Majeed, Aliaa (Iraqi Journal of Science, 2023)
Let M be a prime Γ-ring satisfying abc  abc for all a,b,cM and,  with center Z, and U be a Lie (Jordan) ideal. A mapping d :M Mis called Γ- centralizing if u d u Z  [ , ( )] for all uU and  .In this paper, we studied Lie and Jordan ideal in a prime Γ - ring M together with Γ -centralizing derivations on U.